Regularity and Cointegration in Demand Systems - Kurt Kratena; Michael Wüger (Austrian Institute of Economic Research (WIFO), 1998)
This paper deals with the regularity problem in the Almost Ideal Demand System (AIDS) in terms of the boundedness of the budget shares within the [0,1] interval. The violation of "cointegration accounting" can be seen just as another consequence of irregularity. The discussion of modifications in the PIGLOG cost functions leads to the proposition of a modified dynamic PIGLOG formulation, from which a system of budget shares can be derived, which ensures regularity and validity of "cointegration accounting". A special feature of the resulting share equations is the divergence from the time path of the AIDS shares over time.
Keywords: D11; D12; C30; C32; 330; AIDS mode; PIGLOG specification; cointegration; Konsumtheorie; Importnachfrage; Theorie; Österreich